2011
DOI: 10.1007/s00383-010-2847-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of splenic volume with hematological parameters, splenic vein diameter, portal pressure and grade of varices in extrahepatic portal vein obstruction in children

Abstract: Splenic volume has a weak correlation with splenic vein diameter, but does not correlate with portal pressure or the grade of varix. Splenic vein diameter has a statistically significant correlation with the percentage of portal pressure reduction following a leino-renal shunt. There is a statistically significant negative correlation between the splenic volume and the total leukocyte count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…A recent study showed that spleen volume combined with a biochemical marker (eg, platelet count and/or albumin) can predict the presence of varices in patients with CLD . Meanwhile, in pediatric patients with extrahepatic portal vein obstruction, spleen volume does not correlate with the grade of varices . We speculate that spleen volume will increase with PH development; however, it might not be useful by itself for the assessment of severe GEVs.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study showed that spleen volume combined with a biochemical marker (eg, platelet count and/or albumin) can predict the presence of varices in patients with CLD . Meanwhile, in pediatric patients with extrahepatic portal vein obstruction, spleen volume does not correlate with the grade of varices . We speculate that spleen volume will increase with PH development; however, it might not be useful by itself for the assessment of severe GEVs.…”
Section: Discussionmentioning
confidence: 72%
“…Intraoperative PVP measurement PVP was measured during total anesthetized surgery by inserting a polyvinyl chloride catheter into the main portal vein through the right gastroepiploic vein. [28][29][30] By connecting a pressure transducer to the catheter with the external zero reference set at the midaxillary line, PVP level was shown on the monitor (IntelliVue MP60; Philips Medical Systems) and recorded 30 s later after stabilization. Portal hypertension was defined as a PVP level of over 15 mmHg.…”
Section: Image Analysismentioning
confidence: 99%
“…Editor, I read the recent publication on correlation of splenic volume with hematological parameters, splenic vein diameter, portal pressure and grade of varices in extrahepatic portal vein obstruction with a great interest [1]. Singh et al [1] found that ''larger splenic volumes were associated with lower hemoglobin and platelet counts and significantly lower total leukocyte counts.''…”
mentioning
confidence: 99%
“…Singh et al [1] found that ''larger splenic volumes were associated with lower hemoglobin and platelet counts and significantly lower total leukocyte counts.'' I agree with the finding but I would like to draw attention to some facts.…”
mentioning
confidence: 99%